Accountants’ Capability Requirements for Fraud Prevention and Detection in Nigeria - Popoola, Oluwatoyin Muse Johnson; Che-Ahmad, Ayoib B.; Samsudin, Rose Shamsiah; Salleh, Kalsom; Babatunde, Dorcas Adebola (International Journal of Economics and Financial Issues, 2016)
This paper investigated the capability requirements as represented by Knowledge (KR) and Skills (SR) requirements and competence requirement as represented by Fraud risk assessment (FRA) of a forensic accountant and auditor in the Nigerian public sector. In addition, this study explored whether the forensic accountant possesses higher levels of SR, KR and FRA requirements than the auditor in an evolving area of fraud prevention, detection and response. The study embraced positivist paradigm, adopted cross-sectional design and a survey method. Of the 400 questionnaires distributed, 363 questionnaires were returned and out of which 316 questionnaires were retained for further analysis. The variables are operationalized with a total of 29 observable items, which included demography information. The study results confirmed the significant positive relationship between Skill and Knowledge on Fraud Risk Assessment. Furthermore, the findings showed that the forensic accountant has significantly higher levels of Knowledge, Skill and Fraud Risk Assessment than auditor regarding issues of fraud prevention, detection and response. The implication of this study might result in the overall reduction of corruption and fraud in the public sector, enhancement of institutional, regulatory, ethical and legal framework, and create awareness amongst the accounting and auditing systems management in Nigeria especially and similar developing nations in general. The results add value to the theory, method and practice on fraud prevention, detection, and response by introducing the empirical examination of KR, SR, and FRA in a workplace. Keywords: Capability requirement, task performance, fraud prevention and detection, government policy and regulation JEL Classifications: M40, M41, M42, M48, M49